Vertigo in internist's practice - O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2007)
Vertigo is a problem faced by doctors of all specialties. Vertigo is diagnosed in 30% of people over 65 years and 50% of individuals aged over 80 years. This symptom affects quality of life, may cause falls and traumas, lead to impaired functioning and even disability. There are three main vertigo types: "true", or systemic; lipothymic states and syncope of various origin; vertigo of combined origin (trait and stature disorders), plus the fourth variant, psychogenic vertigo. Vertigo type identification is based on detailed complaint analysis. Therapeutic strategy should be aimed at eliminating vertigo causes, symptom alleviation, and patient's rehabilitation. Therapeutic agents act on the levels of vestibular receptors or central vestibular structures. One of effective agents for symptomatic therapy is betahistine hydrochloride.